RADIO-WAVES REFLECTION AT REMOTE SENSING OF UNDERLYING COVERS - L. P. Ligthart; A. I. Kozlov; A. I. Logvin; I. V. Avtin (Научный вестник МГТУ ГА, 2019)
Monitoring technologies are rapidly developing at present and allow to extract and use non-coordinate information about objects. Noncoordinate information is the information about the type and properties of an object under study. Remote sensing is the main method of solving monitoring problems where special positioning belongs to the radar methods, based on space-time processing of signals and, in particular, on methods of radio polarimetry. It is necessary to have information about the surface in order to solve the monitoring task. The slightest changes in the electrical and physical properties of such areas as salinity, humidity, soil composition, etc. will lead to a change in the basic electrodynamics of the surface, notably its complex dielectric permittivity. The article demonstrates the precise solutions to the problems of radio-waves reflection from a layered surface with various laws of changes of the complex permittivity  in depth. Media with exponential and quadratic laws of variation  for arbitrary angles of incidence of the radio wave on the surface are considered. Precise decision is obtained for layered media with the law of change in the complex permittivity the polynomial and linear characteristics. A similar problem for the parabolic layer is considered separately. The detailed analysis of radio waves reflection from the medium with a matching layer is carried out. The nature of the electromagnetic field inside the transition layer is studied in detail. The article is illustrated by the graphs showing the dependences of an electromagnetic wave reflection coefficient on the layered medium with linear and exponential laws of variation of the complex dielectric constant over depth.